Analisis Pengaruh Fund Longevity, Fund Size, dan Family Size terhadap Kinerja Reksadana pada Reksadana Saham di Indonesia Periode 2016-2019 - Tubety, Ari; Amirah (Konsentrasi: Jurnal Manajemen dan Bisnis, 2021)
This study aims 1). To analyze the effect of Fund Longevity on the performance of equity funds, 2). To analyze the effect of Fund Size on the performance of equity funds, 3). To analyze the effect of Family Size on stock mutual funds performance, 4). To analyze the effect of Fund Longevity, Fund Size, and Family Size simultaneously on the performance of equity funds.The method used in this research is quantitative research. Equity mutual fund performance measurement uses the Sharpe method. While the data analysis method used is multiple linear regression using statistical software SPSS 22. The results of this study indicate that 1). Fund Longevity has a significant negative effect on the performance of equity funds, 2). Fund Size has a positive and insignificant effect on the performance of equity funds, 3). Family Size has a significant negative effect on the performance of equity funds, 4). Fund Longevity, Fund Size, and Family Size simultaneously have a positive effect on the performance of equity funds.